2005
DOI: 10.1016/j.neuron.2005.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease in the Presynaptic Calcium Current Is a Major Cause of Short-Term Depression at a Calyx-Type Synapse

Abstract: Repetitive nerve firings cause short-term depression (STD) of release at many synapses. Its underlying mechanism is largely attributed to depletion of a readily releasable vesicle pool (RRP) and a decreased probability of releasing a readily releasable vesicle during an action potential. Which of these two mechanisms is dominant and the mechanism that decreases the release probability remain debated. Here, we report that a decreased release probability is caused by a calcium-induced inhibition of presynaptic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
229
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(253 citation statements)
references
References 61 publications
22
229
2
Order By: Relevance
“…Furthermore, given that replenishment rates of slowly releasing vesicles are quite high and release probability is low, slowly releasing vesicles may especially contribute to the steady-state postsynaptic responses during repetitive stimulation. Synaptic responses under a long-lasting train of APs are difficult to study, because other factors such as presynaptic Ca 2ϩ channel inactivation may contribute to synaptic depression (Forsythe et al, 1998;Xu and Wu, 2005) (but see Takahashi et al, 2000). Furthermore, when the intervals between stimulations are increased, calmodulin-independent recovery of the fast-releasing vesicles (time constant of 4 -6 s) contributes more significantly to the synaptic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given that replenishment rates of slowly releasing vesicles are quite high and release probability is low, slowly releasing vesicles may especially contribute to the steady-state postsynaptic responses during repetitive stimulation. Synaptic responses under a long-lasting train of APs are difficult to study, because other factors such as presynaptic Ca 2ϩ channel inactivation may contribute to synaptic depression (Forsythe et al, 1998;Xu and Wu, 2005) (but see Takahashi et al, 2000). Furthermore, when the intervals between stimulations are increased, calmodulin-independent recovery of the fast-releasing vesicles (time constant of 4 -6 s) contributes more significantly to the synaptic responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inactivation of presynaptic Ca 2ϩ channels might contribute to synaptic depression during lowfrequency stimulation by APs (Xu and Wu, 2005) (but see Takahashi et al, 2000). In this study, analysis was restricted to synaptic responses during high-frequency stimulation (Ն100 Hz), in which presynaptic Ca 2ϩ currents show little inactivation and depletion of releasable vesicles is the determining factor for synaptic depression (Wu and Borst, 1999).…”
Section: Synchronous and Asynchronous Release During A 100 Hz Train Omentioning
confidence: 94%
“…Presynaptic recordings from the calyx of Held have shown that prolonged high-frequency stimulation reduces calcium entry ) that can contribute to depression. Remarkably, small numbers of stimuli at low frequency can reduce calcium entry sufficiently that it can substantially reduce synaptic transmission (Xu and Wu 2005). At the calyx of Held synapse, short-term depression is largely a result of decreased calcium entry for activation frequencies of ,30 Hz and primarily a result of depletion at frequencies .100 Hz; at intermediate frequencies both mechanisms contribute (Xu and Wu 2005).…”
Section: Inactivation Of Calcium Channels and Other Mechanisms Of Depmentioning
confidence: 99%
“…Remarkably, small numbers of stimuli at low frequency can reduce calcium entry sufficiently that it can substantially reduce synaptic transmission (Xu and Wu 2005). At the calyx of Held synapse, short-term depression is largely a result of decreased calcium entry for activation frequencies of ,30 Hz and primarily a result of depletion at frequencies .100 Hz; at intermediate frequencies both mechanisms contribute (Xu and Wu 2005). Studies of synaptic transmission in cultured superior cervical ganglion neurons expressing calcium channels that either possess or lack calmodulin-dependent inactivation suggest that depression can arise from calcium channel inactivation mediated by calmodulin (Mochida et al 2008).…”
Section: Inactivation Of Calcium Channels and Other Mechanisms Of Depmentioning
confidence: 99%
“…Short-term depression of synaptic release has been traditionally accredited to depletion of the release-ready vesicle pool (von Gersdorff and Borst 2002, Wong et al 2003, Zucker and Regehr 2002, Wang and Kaczmarek 1998, although other mechanisms like receptor desensitization (Wong et al 2003) may be involved. At the large calyx of Held synapse, it has been shown that short-term synaptic plasticity is also achieved by a mechanism involving the regulation of presynaptic Cav2.1 Ca 2+ currents , Tsujimoto et al 2002, like calcium channel inactivation (Xu and Wu 2005, Muller et al 2008, Di Guilmi et al 2011 and calcium channel inhibition by presynaptic metabotropic glutamate receptor (von Gersdorff et al 1997, Takahashi et al 1996 or AMPA receptors (Takago et al 2005). Hennig et al Ca 2+ -dependent facilitation (CDF) of Cav2.1 channels is an important mechanism required for normal synaptic plasticity at fast synapses in the mammalian CNS.…”
Section: C5 Effects Of Fhm1 Mutation On Synaptic Plasticitymentioning
confidence: 99%